Equal Pay For Equal Work Sebagai Sarana Penjamin Ham Dalam Ketenagakerjaan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The economy is one of the most important elements in advancing a country, in the economy of course regulates employers and labor. This is summarized in the term employment. In employment, of course, guarantees have been made that require equality by means of labor inspection, but what happens in the field still illustrates inequality in the world of labor. So this research takes a concept called equal pay for equal work in a means of guaranteeing equality and is linked to human rights. This research uses descriptive qualitative methodology. By bringing the problem of how equal pay for equal work in human rights issues and how the correlation between equal pay for equal work on labor law and positive in Indonesia.